KEDISIPLINAN BELAJAR SISWA PADA MATERI KEBUMIAN MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TRIO UNIT DUEL TEAM GAMES TOURNAMENT (TUDTGT) - Lukman, Inayah; Azhar, Azhar; Ma?aruf, Zuhdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to describe the discipline of student learning by applying thecooperative learning model of the trio unit type duel team games tournament(TUDTGT) to earth subject. This type of research is descriptive research. The subjectsin this study were students of class X.MO 2, totals are 33 students. Data collectingtechniques in this study such as observations with data collection research instrumentsare the form of observation rubrics and observation tables. Data analysis of the resultsof the study was descriptive data analysis and data analysis of student learningdiscipline. The results showed students’ learn discipline of class X.MO 2 SMK TarunaSatria Pekanbaru by applying Cooperative Learning Model Trio Unit Duel TeamGames Tournament Type (TUDTGT) on earth subject reaches 81% of the averagepercentage of ideal criteria. This is based on the number of students in very disciplinecriteria with 81% - 100% percentage is the higher compared with other criteria.Keywords: Cooperative Learning, Trio Unit Duel Team Games Tournament, Student LearningDiscipline